Legal Considerations of the Notary Supervisory Board Regarding the Concept of Carefulness and Legal Consequences For Deeds Made Based on False Information - Ahmad Wildani Taufiqi; Rachmi Sulistyarini; Fathul Laila (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This research examines the legal responsibility of notaries for authentic deeds made based on false statements from the perspective of the Regional Supervisory Council of Southeast Sulawesi. The main issues explored are how the MPW interprets the phrase "careful and thorough" in Article 16 paragraph (1) letter (a) of the Notary Act and how such interpretation affects the validity of deeds and the notary's legal liability. The study employs a normative juridical method using statutory, conceptual, and analytical approaches that link positive legal norms with MPW Decision No. 6/PTS/MPWN_Prov.Sultra/I/2025 jo 04/PTS/MPWN_Prov.Sultra/VI/2025. Findings indicate that the MPW considers the notary's failure to verify documents and parties' identities as culpa lata (gross negligence), rendering the deed invalid as an authentic instrument. The results demonstrate that the prudential principle in notarial practice functions not merely as an administrative norm but as an ethical-professional standard that ensures the integrity of authentic deeds. The study highlights the urgency of establishing a Code of Prudence as a standardized ethical assessment tool to strengthen supervision, prevent inter-council disparities, and balance public protection with professional security.